Малютка Волк - гроза Морей - Уайброу Иан (Малютка Волк, 2009)
Экземпляры: Архангельская биб-ка (20190130) / Инвентарный номер: 42857 / Цена: 225.16 / Сис.шифр: И (Англ.) / Авт.знак: У13 / ГРНТИ: 17.82 / ББК: 84(4Вел)